Assessment of caries frequency and severity in immature permanent first molar teeth using panoramic radiograph in Elazig city, Turkey - Yildiz, Semsettin; Ataş, Osman (Harran Üniversitesi, 2024)
Aims: Considering the importance of permanent first molars (PFM), this study aims to evaluate the prevalence and severity of caries in permanent first molars with exposed immature root tips on panoramic radiographic images. Materials and Methods: Panoramic x-rays (Planmeca ProMax 3D Mid) taken for diagnosis and treatment purposes from 799 individuals in the 6-9 age group were evaluated retrospectively. Caries prevalence and severity in immature PFMs were determined using the International Caries Classification and Management System (ICCMSTM) as a reference. Statistical comparisons were made through the statistical program SPSS 26 (SPPS Inc, Chicago, IL, USA). Chi-square analysis was used to compare the presence of dental caries in individuals according to age, gender, and tooth position. The study determined the statistical significance level as p0.05), and there is a statistically significant difference between individuals' evaluations of the presence of caries according to the position of their teeth (p

Amaç: Bu çalışmada, daimi birinci molar dişlerin (PFM), önemi göz önünde bulundurularak, panaromik radyografik görüntüler üzerinde olgunlaşmamış kök ucu açık daimi birinci büyük azı dişlerde çürük prevalansı ve şiddetinin değerlendirilmesi amaçlanmaktadır. Materyal ve Method: 6-9 yaş grubundaki 799 bireyden tanı ve tedavi amacıyla çekilmiş panoromik röntgenler (Planmeca ProMax 3D Mid) üzerinde retrospektif olarak deg?erlendirildi. Uluslararası Çürük Sınıflandırması ve Yönetim Sistemi (ICCMSTM) referans alınarak olgunlaşmamış PFM’lerde çürük prevelansı ve şiddeti belirlendi. İstatistiksel karşılaştırmalar SPSS 26 (SPPS Inc, Chiago, IL, ABD) istatistik programı aracılığı ile gerçekleştirilmiştir. Bireylerin diş çürükleri varlığının yaş, cinsiyet ve diş konumuna göre karşılaştırılmasında ki-kare analizinden yararlanılmıştır. Araştırmada istatistiksel anlamlılık düzeyi p
Elazığ İlinde Olgunlaşmamış Daimi Birinci Molar Dişlerde Çürük Sıklığı ve Şiddetinin Panaromik Röntgen ile Değerlendirilmesi
Keywords: Paedodontics; Çocuk Diş Hekimliği